Comparative Global Metabolome Profile and Transcriptome Sequence Analysis of the Rough and Smooth Peel of the Orah Mandarin (Citrus reticulata) - Hongming Liu; Chunrui Long; Xiaomeng Fu; Shaohua Wang; Yuqiang Lou; Jianmei Dong; Meichao Dong; Jiamei Mao; Jiandong Yang; Hongxia Yang; Yuxia Du; Xianyan Zhou (Horticulturae)
Background: The Orah mandarin is an economically important variety of Citrus reticulata for citrus growers in Yunnan Province, China. Generally, the fruit peel is smooth, an attractive feature for consumer preferences. Recently, rough peels have been observed in several orchards, making the fruit aesthetically less desirable. Little is known about the mechanism of rough skin development. Methods: In this study, we used global metabolomics and a comparative transcriptomic approach to characterize the differences between smooth (CK) and rough (CP) Orah mandarin peels. Results: Our results indicate that CP fruits have a significantly larger diameter, peel weight and thickness, total soluble solids, and titratable acid content compared to CK. Metabolomic analysis detected 810 metabolites, of which 192 were differentially accumulated in CP and CK. CP is characterized by higher levels of flavonoids, amino acids and derivatives, terpenoids, and alkaloids. We also report nine compounds detected exclusively in CP, including dambonitol, 3-methyl-L-histidine, deacetylnomilinic acid, obacunoic acid, and 6-O-acetylarbutin. The transcriptome results showed that the expression of genes enriched in flavonoids, lipid, and amino acid metabolism and related pathways were consistent with the metabolome profiles. We also discuss the possible involvement of phytohormones in peel roughening. Conclusions: Overall, we present, for the first time, a detailed comparative metabolome and transcriptome profile in smooth and rough Orah mandarin peels. Our data and discussion highlight the potential mechanisms and provide a theoretical basis for the improvement of rough peel Orah mandarins.